B cell academy of the gut: an update on gut associated germinal centre B cell dynamics - Christopher Wichmann; Elisa Wirthgen; Carla R. Nowosad; Jan Däbritz (SpringerOpen, 2024)
Abstract Background The gut is an environment in which the immune system closely interacts with a vast number of foreign antigens, both inert such as food and alive, from the viral, bacterial, fungal and protozoal microbiota. Within this environment, germinal centres, which are microanatomical structures where B cells affinity-mature, are chronically present and active. Main Body The functional mechanism by which gut-associated germinal centres contribute to gut homeostasis is not well understood. Additionally, the role of T cells in class switching to immunoglobulin A and the importance of B cell affinity maturation in homeostasis remains elusive. Here, we provide a brief overview of the dynamics of gut-associated germinal centres, T cell dependency in Immunoglobulin A class switching, and the current state of research regarding the role of B cell selection in germinal centres in the gut under steady-state conditions in gnotobiotic mouse models and complex microbiota, as well as in response to immunization and microbial colonization. Furthermore, we briefly link those processes to immune system maturation and relevant diseases. Conclusion B cell response at mucosal surfaces consists of a delicate interplay of many dynamic factors, including the microbiota and continuous B cell influx. The rapid turnover within gut-associated germinal centres and potential influences of an early-life window of immune system imprinting complicate B cell dynamics in the gut.